Analisis Kepesertaan Jaminan Sosial Ketenagakerjaan pada Pekerja Sektor Informal Di Kota Pekalongan - Arum Ardianingsih; Juandy Seiver Langelo; Pandu Wicaksono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
Pekalongan is located on the nort-central coast and has a workforce of 95.581. the productive age population is generally the labor force that requires employment. Pekalongan, which is famous as a batik city, has 21.979 micro, small and medium enterprises(MSMEs). This is enough to help the population of productive age to be absorbed in the informal sector. Workers in both the formal and non-formal sectors get a salary or wages or income and social security benefits. This study aims to see the level of participation of informal workers in Pekalongan. This research is a qualitative research with triangulation analysis technique. Research data is presented descriptively. Researchers found that employment social security participation by informal sector workers in Pekalongan was still low due to the lack of socialization provided, ignorance of the procedures for registering BPJS membership and the perceived high cost of social security contributions by most informal workers. Keywords: Employment social assurance, informal workers, Pekalongan